Project Work Implementation in a Virtual Colombian Public University Environment - Yakelin Salinas (Asociación Colombiana de Profesores de Ingles, 2011)
This article is a report of the steps followed in the pedagogical intervention of project work developed with a group of students involved in a virtual program at a public Colombian University. It is part of a wider investigation in which the purpose was to explore and describe the roles of teachers, students and discussion boards while implementing project work. The implementation was based on an adaptation of the Project Planning Form from the Buck Institute for Education. This form allowed doing the project in a procedural and organized way. Based on the achievements of the implementation, I give some recommendations to teacher researchers interested in the field.